Testing of leakage current failure in ASIC devices exposed to total ionizing dose environment using design for testability techniques - Mohamed, Assem Mohamed Alaa El Din Ali (AUC Knowledge Fountain, 2020)
Due to the advancements in technology, electronic devices have been relied upon to operate under harsh conditions. Radiation is one of the main causes of different failures of the electronics devices. According to the operation environment, the sources of the radiation can be terrestrial or extra-terrestrial. For terrestrial the devices can be used in nuclear reactors or biomedical devices where the radiation is man-made. While for the extra- terrestrial, the devices can be used in satellites, the international space station or spaceships, where the radiation comes from various sources like the Sun. According to the operation environment the effects of radiation differ. These effects falls under two categories, total ionizing dose effect (TID) and single event effects (SEEs). TID effects can be affect the delay and leakage current of CMOS circuits negatively. The affects can therefore hinder the integrated circuits' operation. Before the circuits are used, particularly in critical radiation heavy applications like military and space, testing under radiation must be done to avoid any failures during operation. The standard in testing electronic devices is generating worst case test vectors (WCTVs) and under radiation using these vectors the circuits are tested. However, the generation of these WCTVs have been very challenging so this approach is rarely used for TIDs effects. Design for testability (DFT) have been widely used in the industry for digital circuits testing applications. DFT is usually used with automatic test patterns generation software to generate test vectors against fault models of manufacturer defects for application specific integrated circuit (ASIC.) However, it was never used to generate test vectors for leakage current testing induced in ASICs exposed to TID radiation environment. The purpose of the thesis is to use DFT to identify WCTVs for leakage current failures in sequential circuits for ASIC devices exposed to TID. A novel methodology was devised to identify these test vectors. The methodology is validated and compared to previous non DFT methods. The methodology is proven to overcome the limitation of previous methodologies.